Evaluasi Penggunaan Dana Desa dan Alokasi Dana Desa - Suharyono Suharyono (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Development is the most important thing in the countryside. All that can be seen from the way the government manages its finances, including village funds and village funds. This study discusses the evaluation of the use of village funds and allocation of funds. The type of research used is descriptive qualitative. The results of this study indicate how the use of village funds and village funds in BM has not been used to its full potential, because there are still a number of program activities that are not realized. While unrealized activities are management of village-owned libraries, security capacity building and improvement, construction / repair / construction of buildings, construction of village information systems, education programs, and disaster management activities.